Numerical Simulation of Underwater Shock Wave Propagation in the Vicinity of Rigid Wall Based on Ghost Fluid Method - Ru-Chao Shi; Rui-Yuan Huang; Guang-Yong Wang; You-Kai Wang; Yong-Chi Li (Shock and Vibration)
This paper presents numerical simulation of underwater shock wave propagation nearby complex rigid wall. The Ghost Fluid Method (GFM) for the treatment of complex rigid wall is developed. The theoretical analysis on the GFM-based algorithm and relevant numerical tests demonstrate that the GFM-based algorithm is first-order accurate as applied to complex rigid wall. A large number of challenging numerical tests show that the GFM-based algorithm is robust and quite simple in various practical problems. The numerical results on shock wave propagation in the vicinity of rigid wall are verified by comparing to exact solution and the results by body-fitted-grid method.